2020
DOI: 10.1186/s43044-020-00077-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal diabetes and obesity on fetal cardiac functions

Abstract: Background: In several developing industrial countries, the incidence of obesity among populations is spreading quickly and dramatically; also, the frequency of maternal obesity is in continuous elevation, which represents a considerable public health problem. Maternal hyperglycemia is a common gestational risk factor for the fetus. Several studies proposed that maternal DM and obesity lead to intrauterine impacts which induce changes in the fetal myocardium, and the pre-pregnancy obesity and diabetes are acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Reactive oxidative species also causes excess lipid peroxidation and cardiac fibrosis which is another reason behind dysfunctional cardiovascular programming ( 35 , 39 , 40 ). Bayoumy et al ( 41 ) measured cardiac function in fetuses of obese, diabetic, and normal pregnant women by employing tissue Doppler imaging at 30 weeks gestation. Fetuses of obese and diabetic pregnant women had lower systolic and diastolic function compared to women with normal BMI, indicating weakened cardiovascular function in developing fetuses owing to maternal obesity.…”
Section: Complications Of Maternal Obesity In the Mothermentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxidative species also causes excess lipid peroxidation and cardiac fibrosis which is another reason behind dysfunctional cardiovascular programming ( 35 , 39 , 40 ). Bayoumy et al ( 41 ) measured cardiac function in fetuses of obese, diabetic, and normal pregnant women by employing tissue Doppler imaging at 30 weeks gestation. Fetuses of obese and diabetic pregnant women had lower systolic and diastolic function compared to women with normal BMI, indicating weakened cardiovascular function in developing fetuses owing to maternal obesity.…”
Section: Complications Of Maternal Obesity In the Mothermentioning
confidence: 99%
“…These observations of cardiovascular effects on offspring are difficult to attribute in entirety to abnormal glucose metabolism in obese mothers. Thus, further investigation is warranted to better understand the overall impact of maternal obesity on fetal health status ( 41 ).…”
Section: Complications Of Maternal Obesity In the Mothermentioning
confidence: 99%
“…Tissue Doppler imaging (TDI) can elaborate on the presence of early foetal cardiac dysfunction, even in the absence of structural abnormalities. The ability to detect early cardiac dysfunction is valuable in monitoring and timing the delivery of complicated preterm pregnancy[ 50 ]. Two-dimensional speckle-tracking echocardiography (STE) could offer an additional benefit over conventional echocardiography to detect subclinical unfavourable changes in myocardial function in this population.…”
Section: Cardiac Evaluation Of Foetuses and Idmsmentioning
confidence: 99%
“…However, using standard echocardiography to assess fetal cardiac performance (Mitral and tricuspid annular plane systolic excursions, mitral and tricuspid early velocity, late velocitiy, and early and late diastolic filling ratio), they demonstrated that all fetuses seem to be healthy. 33 Additionally, Kulkarni et al also reported that two-dimensional speckle-tracking echocardiography measures of myocardial function in fetuses of diabetic and obese women were generally more consistent than traditional Doppler echocardiography parameters. 34 In this study, conventional echocardiographic techniques were used to assess fetal diastolic functions.…”
Section: Discussionmentioning
confidence: 99%